P1-S2.73 Exploring the relationship between Rural-to-Urban circular migration and HIV: a qualitative study of migrants and persons living with HIV in North India. (10th July 2011) - Rai, T; Lambert, H; Piot, P; Agarwal, K; Ward, H
Abstract : Background: Migrant workers may be at increased risk of acquiring HIV and have been described as a potential bridge between high- and low-prevalence geographic areas and groups. The National AIDS Control Organisation of India has prioritised interventions for migrant workers with the aim of curbing the spread of HIV from high to low prevalence parts of the country. We describe links between migration and HIV and explore variations in risk between migrants. Methods: A qualitative study in Allahabad district, Uttar Pradesh, India. Interviews, focus groups and observations were carried out in two rural villages with high temporary out-migration of men, and in an HIV treatment centre in Allahabad. For this study we defined migrants as those who leave and return to their place of origin once or more in a year. Participants included key informants (14), rural migrant men (20), and men and women living with HIV/AIDS (PLHAs) (30). Results: PLHA and migrant men described a range of ways in which migration could lead to an increase in the potential or actual risk of acquiring HIV. These included separation from wives and opportunities for other relationships, exposure to sexual abuse in destination workplaces, sex between men, and exposure to unregulated injections. These risks varied according to destination, with less opportunity for sexual risk-taking in factories where men were housed in closely-supervised factory accommodation. HIV in turn affected migration with a particular impact on the ability to make money and care for families. For some men illness or the fear of becoming unwell limited further migration, and thus reduced income; others increased migrant labour in order to plan for an uncertain future for their dependents. An HIV diagnosis meant some lucrative international destinations became inaccessible, so they moved elsewhere for work. Conclusions: Labour migration can increase vulnerability to infection for migrants and their families. However, this relationship appears to be more complex than is often assumed. Unprotected heterosexual intercourse may not be the only way in which migration increases HIV risk as there are numerous other risky encounters that migrant workers may have due to their circumstances. Planned programmes to increase HIV awareness and promote condom use at destination and source locations have to be combined with a systematic examination of the effect of social and sexual networks and power relationships in the labour market.